Direct Collapse to Supermassive Black Hole Seeds with Radiative Transfer: Isolated Halos. Issue 3 (10th February 2018) - Luo, Yang; Ardaneh, Kazem; Shlosman, Isaac; Nagamine, Kentaro; Wise, John H; Begelman, Mitchell C
Abstract: Direct collapse within dark matter haloes is a promising path to form supermassive black hole seeds at high redshifts. The outer part of this collapse remains optically thin. However, the innermost region of the collapse is expected to become optically thick and requires to follow the radiation field in order to understand its evolution. So far, the adiabatic approximation has been used exclusively for this purpose. We apply radiative transfer in the flux-limited diffusion (FLD) approximation to solve the evolution of coupled gas and radiation for isolated haloes. We find that (1) the photosphere forms at 10 −6  pc and rapidly expands outwards. (2) A central core forms, with a mass of 1 M⊙, supported by gas pressure gradients and rotation. (3) Growing gas and radiation pressure gradients dissolve it. (4) This process is associated with a strong anisotropic outflow; another core forms nearby and grows rapidly. (5) Typical radiation luminosity emerging from the photosphere is 5 × 10 37 –5 × 10 38  erg s −1, of the order the Eddington luminosity. (6) Two variability time-scales are associated with this process: a long one, which is related to the accretion flow within the central 10 −4 –10 −3  pc, and 0.1 yr, related to radiation diffusion. (7) Adiabatic models evolution differs profoundly from that of the FLD models, by forming a geometrically thick disc. Overall, an adiabatic equation of state is not a good approximation to the advanced stage of direct collapse, because the radiation is capable of escaping due to anisotropy in the optical depth and associated gradients.